The Impact of Strengthening Agricultural Extension Services : Evidence from Ethiopia - Buehren, Niklas; Goldstein, Markus; Molina, Ezequiel; Vaillant, Julia (World Bank, Washington, DC, 2018)
Extension services have been implemented on a large scale in developing countries for decades. However, there is little evidence on their impact on the productivity and welfare of farmers. Our study aims to begin to fill this evidence gap with the goal of identifying and encouraging the uptake of best practices for the delivery of extension services by governments.Our findings suggest that strengthening extension services to make them more responsive to the needs of farmers can induce a switch to more commercial, market-oriented agriculture.Female-headed households seem to have benefited equally from the extension services project but it did not contribute to reducing the gender gap in agricultural outcomes as their initial levels of wealth and consumption, as well as labor and capital endowments were lower.Additional research is required to identify extension services designs that contribute to closing the gender gap, by addressing more specifically the challenges faced by women in areas such as labor and capital endowment.